Exploring the Intersection of Desire and Disability in Margarita with a Straw - Michelle Philip (Andalas International Journal of Socio-Humanities, 2023)
This research paper explores the theme of desire and disability in director Shonali Bose’s film Margarita with a Straw. Through a close analysis of the film, the paper proposes to examine how the protagonist, Laila, a young woman with cerebral palsy, navigates her desires and relationships while dealing with the challenges posed by her disability. It is my contention that the film challenges the dominant narrative of disability as asexuality and incapable of experiencing love or sexual desire while portraying Laila's sexuality and desire as a normal and important part of her life. Additionally, the paper examines how Laila's intersectional identity as a disabled, bisexual woman complicates her desires and relationships. The film emphasises the value of recognising and addressing the sexuality and needs of handicapped people via Laila's character. Ultimately, the paper argues that Margarita with a Straw offers a nuanced and empowering portrayal of disability and desire that challenges ableist and heteronormative assumptions about sexuality and relationships. Overall, this study seeks to add to the expanding body of knowledge about the relationship between disability and sexuality and emphasises the need for change in the portrayal of disability in mainstream media.